ADHESION-INDUCE PROTEIN TYROSINE PHOSPHORYLATION IS ASSOCIATED WITH INVASIVE AND METASTATIC POTENTIALS IN B16-BL6 MELANOMA CELLS - Yan, Chunhong; Han, Rui (Chinese Journal of Cancer Research, 2013)
Objective: The interaction of cancer ceil with extracellular matrix (ECM) happens as an earlier and specific event in the invasive and metastatic cascade. To explore the key element(s) in cancer metastasis and observe the celI-ECM interaction and its role. Methods: To interrupt the celI-ECM interaction by suppression of adhesion-induced protein tyrosine phosphorylation with protein tyrosine kinase inhibitor genistein in B16-BI6 mouse melanoma cells. Results: When B16-BL6 cells attached to Matrigel, a solubilized basement membrane preparation from EHS sarcoma, a 125 kDa protein increased its phosphotyrosine content dramatically. In contrast, when the cells were pretreated with 20gM or 30 ILM genistein for 3 days, it was revealed a less increase in the phosphotyrosine content of this 125 kDa protein in response to cell attachment to ECM was revealed with immunoblot analysis. Accompanied by the lower level of adhesion-induced protein tyrosine phosphorylation the gehistein-treated cells exhibited a decrease in their capabilities of adhesion to Matrigel and invasion through reconstituted basement membrane. The potentials of and forming lung metastatic nodules were also shown to be decreased dramatically in these genistein-treated cells. Conclusion: It was suggested that protein tyrosine phosphorylation in celI-ECM interaction might be associated with invasive and metastatic potentials in cancer cells.